The impact of early life experiences on inhibitory control and working memory - Dydenkova, Eva; McGlone, Francis; Mayorova, Larisa; Nikolaeva, Elena (Frontiers in Psychology, 2024)
Introduction Adverse childhood experiences (ACEs) are a general term for a large group of nonequivalent situations that have the potential to traumatise a child. This risk factor is caused by a sensitive period of brain development, which is based on myelination, creation of synaptic connections and pruning. Dramatic environmental events during this period, such as history of institutionalisation, can disrupt optimal developmental pathways, leaving biological scars for life. Methods The focus of this study was to investigate the impact of institutionalisation on the development of inhibitory control and working memory in three groups of children matched for age (n = 130; 7.1 ± 2.0 years): (1) early institutionalised (n = 35; age of placement: 6.9 ± 10.6 months; duration of placement: 14.6 ± 10.4 months); (2) late institutionalised (n = 29; age of placement: 49.3 ± 30.6 months; the duration of placement: 16.0 ± 19.4 months); (3) never institutionalised (n = 66). Results Results showed that the early institutionalised group had the lowest scores on tests of inhibitory control (p = 0.03), working memory (p = 0.03) and retrieval-based learning (p = 0.04), while the results of the group of late institutionalised children do not differ significantly from never institutionalised. Discussion The existence of a sensitive period during the first 18 months of a child’s life is discussed, which determines the formation of the retrieval-based learning mechanism and of inhibiting ineffective experience, for which executive functions are responsible.